ANALISIS PENINGKATAN KINERJA MELALUI LEADER MEMBER EXCHANGE DAN KUALITAS HUBUNGAN - PURBUDI WAHYUNI; REFFI SANGI (Jurnal Ekonomi dan Bisnis, 2010)
One of the reasons in performance apprisal research was to evaluate accurately and integratethe overall employer performance. The result expected as a feedback to the problems what isincapable, constrained jobs faced by employer, with the reason how to anticipate the aboveproblems to support the stability and balance of the organization (Dreher and Doughethy, 2003).One of the influenced variables to the performance appraisal was LMX and dyadic qualitymoderated duration. The research at PT. PLN Yogyakarta branch, used with survey method for102 respondents evaluated and analysis by multiple regression. The result a strong indicationin simultineous dyadic quality and has a positive and significant relationship with performanceappraisal, although partially not showed a significant performance appraisal relationship. The resultshowed the higher employer performance appraisal in moderated by the interaction duration. Thisappraisal would be strengthen with the finding of rating different between employer performanceappraisal by interaction duraton and gender. These finding expected could be significant feedbackto the employers and especially to the organization in the final decision processed.Keyword : Leadher Member Exchange (LMX), Dyadic Quality, Duration